Capital investments in the presence of tenancy relations - Andersson, Erik; Larsson, Eric (2019)
The agricultural sector is one of the most important industries in Sweden. About 40% of Sweden's agricultural land is leased out, which means that leased farming is a significant part of Swedish agriculture. Since Sweden joined the EU in 1995, the prices of leasing land have almost doubled. This means that leasing farmers must organize and streamline their businesses to achieve similar results. Therefore, farmers must invest in their businesses.